Plasmon's Fizeau‐dragging effect at the interface of atomic and nano‐composites media. Issue 13 (13th March 2021) - Khan, Gohar Zeb; Ashraf, Imrana; Ullah, Arif; Bacha, Bakht Amin
Abstract: The velocity uncertainty by Fizeaus plasmon dragging‐effect is investigated at the interface of four level atomic medium and Silver Silica (AgSiO2 ) nano‐composites material by using surface plasmon polaritons(SPPs) waves. We measured the real part of the dispersion relation Re ( K sp ) = 1.5 K 0 with probe and control field detunings and Re ( K sp ) = 1.36 K 0 with control field Rabi frequencies ∣Ω1, 2  ∣ / γ . Furthermore, Re ( K sp / K 0 ) = 1.8 with damping rate γ 42 / γ and volume frictional change f m . A large kink in the real part of dispersion relation of SPPs was measured in the large interaction region. The group index is in the range of ±20. The maximum dragging coefficient is ±20. The relative phase difference due to dragging is enhance by factor of −1.5 × 10 −8 rad. The propagation time is measured to be 0.8 ns with both control field Rabi frequencies. The volume fractional change of nano particles, probe/control field detuning and Rabi frequency of control field significantly influence the dragging coefficient, relative phase difference and velocity uncertainty. Including Fizeau‐Dragging effect in the given configuration the velocity uncertainty is measured to be 15 μm/s which is much larger than the velocity width of Kuan et al, used Δ v a = (8 k B Tln 2/ m ) 1/2 = 176 mm/s. The velocity uncertainty could be improved to 0.1 μm/s by taking large ensemble of atomic coherence and large delay/advance in time due to SPPs. Abstract : The velocity uncertainty by Fizeaus plasmon dragging effect is investigated at the interface of four level atomic medium and Silver Silica(AgSiO2 ) nano‐composites material by using surface Plasmon polaritons(SPPs) waves.